LARVICIDAL ACTIVITY OF ESSENTIAL OIL OF GLIRICIDIA SEPIUM LEAF - A., UMADEVI; JALEEL, ABDUL (International Journal of Current Pharmaceutical Research, 2020)
Objective: This study focus at the larvicidal activity of essential oil of Gliricidia sepium leaf Methods: Pharmacological evaluation of leaf was carried out for larvicidal activity. Household mosquitoes of fourth instar larvae were used for the study. The study was carried out for 5 different concentrations for aqueous extract. Results: The aqueous extract shown dose-dependent activity with the maximum larvicidal potential was seen with leaf of essential oil (250 mg/ml). Conclusion: The study is designed to evaluate the larvicidal activity of essential oil of leaf of G. sepium. The relationship between the chemical composition and biological activity of essential oil of G. sepium is confirmed by lethal effect.